MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK MUATAN MATEMATIKA MENGUNAKAN MODEL PJP PADA PESERTA DIDIK KELAS IV SDN TELUK TIRAM 2 - Rahmanika Amalia; Herti Prastitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the low learning activities, as well as students' learning outcomes in learning mathematics using the PJP model. Where this research uses the classroom action research method which is carried out in four meetings, where each meeting has four stages, namely planning, implementation, observation and reflection. The subjects in this research were class IV students at SDN Teluk Tiram 2, with a total of 18 students, consisting of 9 male students and 9 female students. Data collection uses observation techniques, interviews and tests on student learning outcomes. This research shows that the completeness of students' learning outcomes in the pre-test was only 28%, then it increased at the first meeting to 44%, at the second meeting 72%, at the third meeting 94%, until at the fourth meeting it reached 100%. Student activity in meeting I only got 17%, increased in meeting II to 50%, meeting III to 78%, until at the last meeting it reached 100%. Because of this, it can be concluded that the results of this research show that the use of the PJP learning model can improve learning outcomes and learning activities for class IV students at SDN Teluk Tiram 2.